The Effectiveness of Semiotic Innovation on Learning the Al-Gharibah Verse in Increasing Understanding of Tahsin in Koto Kampar Hulu District - Nelvawita, Nelvawita; Evadewi, Evadewi; S, Mochammad Novendri (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to explore the implementation and impact of innovative semiotic strategies in learning Al-Gharibah verses in tahsin in Koto Kampar Hulu District. Al-Gharibah verses, which are linguistically complex and rich in symbolic meaning, demand a more in-depth and innovative approach to improve students' understanding of the Qur'anic text. Koto Kampar Hulu District was chosen as the research location because it has a strong community background in Islamic values and religious education as an integral part of everyday life. This study uses a qualitative approach with a focus on case studies. Data collection methods include participant observation, in-depth interviews, and document analysis related to the curriculum and teaching materials. The results showed that the implementation of innovative semiotic strategies significantly improved teachers' understanding of Al-Gharibah verses. Teachers became more able to associate signs with the meanings they represent and interpret the symbolic context of the verses more deeply. In addition, this approach also increased students' motivation and interest in learning the Qur'anic text, making learning more relevant and interesting for them. This study highlights the importance of integrating educational technology, such as the Tahsin Mubarismani application, as a supporting tool in facilitating the learning of the Al-Gharibah verse. The implications of this study include recommendations for the development of a more in-depth curriculum in incorporating a semiotic approach, ongoing training for teachers, and strengthening collaboration between schools, communities, and related parties to support the sustainability of the implementation of this strategy in religious education.